Progressive Modular Rebalancing System and Visual Cueing for Gait Rehabilitation in Parkinson's Disease: A Pilot, Randomized, Controlled Trial With Crossover - Serrao, Mariano; Pierelli, Francesco; Sinibaldi, Elisabetta; Chini, Giorgia; Castiglia, Stefano Filippo; Priori, Marina; Gimma, Dario; Sellitto, Giovanni; Ranavolo, Alberto; Conte, Carmela; Bartolo, Michelangelo; Monari, Giuseppe (Frontiers in Neurology, 2019)
Introduction. The progressive modular rebalancing (PMR) system is a comprehensive rehabilitation approach derived from proprioceptive neuromuscular facilitation (PNF) principles. PMR training encourages focus on trunk and proximal muscle functions through direct perception, strength, and stretching exercises and emphasizes bi-articular muscle functions to improve gait performance. Sensory cueing, such as visual cues (VC), is one of the longer and better-established technique for gait rehabilitation in PD. Herein, we propose PMR combined with VC for improving gait performance, balance and trunk control during gait in patients with PD. Our assumption herein was that the effect of VC might act on an improved motor performance induced by the PMR treatment. The primary aim of this study was to evaluate whether the PMR system plus VC was a more effective treatment option than standard physiotherapy in improving gait function. The secondary aim of the study was to evaluate the effect of this treatment on the motor disease severity. Design. Two centers, randomized, controlled, observer-blind, crossover study with a four-month washout period. Participants. Forty individuals with idiopathic PD in Hoehn and Yahr stages 1 to 4. Intervention: Eight-week rehabilitation programs consisting of PMR plus VC (treatment A) and conventional physiotherapy (treatment B). Primary outcome measures: Spatiotemporal gait parameters, joint kinematics, trunk kinematics. Secondary outcome measures: UPDRS-III scale scores. Results: The rehabilitation program was well-tolerated by individuals with PD and most participants showed improvements in the gait variables and UPDRS-III scores for both treatments. However, patients who received PMR with VC showed better results of gait function in terms of gait performance (increased step length, gait speed, and joint kinematics), gait balance (increased step width and double support duration), and trunk control (increased trunk motion) than did those receiving conventional physiotherapy. Crossover results still revealed some difference in primary outcomes, but since only 37.5% of patients crossed over between the groups, the results need to be interpreted with great caution. Conclusions: PMR plus VC program could be used to improve gait function and motor severity in individuals with PD.